ChemInform Abstract: Recent Advances on the Synthesis of Hepatitis C Virus NS5B RNA‐Dependent RNA‐Polymerase Inhibitors. Issue 44 (15th October 2015) - Zhao, Can; Wang, Yinhu; Ma, Shutao
Abstract Review: 109 refs.